-5-u=4u

Simple and best practice solution for -5-u=4u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-u=4u equation:


Simplifying
-5 + -1u = 4u

Solving
-5 + -1u = 4u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-4u' to each side of the equation.
-5 + -1u + -4u = 4u + -4u

Combine like terms: -1u + -4u = -5u
-5 + -5u = 4u + -4u

Combine like terms: 4u + -4u = 0
-5 + -5u = 0

Add '5' to each side of the equation.
-5 + 5 + -5u = 0 + 5

Combine like terms: -5 + 5 = 0
0 + -5u = 0 + 5
-5u = 0 + 5

Combine like terms: 0 + 5 = 5
-5u = 5

Divide each side by '-5'.
u = -1

Simplifying
u = -1

See similar equations:

| 4x^2-3=77 | | 3ab-a-2b-2=0 | | 3ab-a=2b+2 | | f(x+y)-f(x-y)=5xy+2y | | 8(-4.5)+7.5=31 | | 3+p=7 | | 4l-2.6=13.4 | | 24uw^5y^2+28u^4w^8= | | -3+9m=-10m | | 3x(x-7)=3+5 | | 9x(9-y)-1=0 | | 2(x-5)-12=2x-22 | | 4a-6b=10 | | 2(x-3)=3x-9 | | c^2=5 | | (3x+1)(x+9)=0 | | 5z+6=8z | | 6j=7j+6 | | 4-9x=-8x | | c^2+9=14 | | 15+4x=30 | | P(t)=6050(1.04)t | | (0.12)x+(0.16)(1-x)=0.125 | | 8x-16=6x-2 | | a^5=0 | | 7-2(-8x+7)=-2(x-5)+7 | | y^2-2x-y=0 | | -9y^2+81y-1=0 | | 2x^2-32x-4=0 | | 7x+18-7x=18 | | j^4+64j^2=0 | | x^2+8x+1=10 |

Equations solver categories